Akuntabilitas Publik Era Digital di Indonesia: Analisis Peluang dan Tantangan - Asrida; Miya Nurohmah (PT. Palem Edukasi Nusantara, 2025)
Digital transformation has brought significant changes to governance by encouraging the creation of more efficient, transparent, and accountable systems. This study aims to analyze the opportunities and challenges of public accountability in the digital era. This study uses a qualitative method with a literature study approach that examines various academic sources and previous research results regarding the use of digital technology to increase transparency, public participation, and the effectiveness of government services. The results of this study found that digitalization opens up significant opportunities to strengthen public accountability through increased information transparency, public participation in oversight, efficiency of public services, and fostering public trust in the government. However, there are other findings in the implementation of digitalization facing several challenges such as the digital divide between regions, low digital literacy of officials and the public, data security and privacy, resistance to bureaucratic culture, regulatory inconsistencies, and the rise of disinformation in the digital space. To address these challenges, the implications of this study are the need for strategic innovation through strengthening regulations and national digital standards, continuously increasing digital literacy, equitable distribution of technological infrastructure across all regions, and the development of a reliable cybersecurity system through the application of technologies such as Blockchain, big data analytics, and multi-factor authentication. In addition, international collaboration with global cyber defense centers such as the NATO CCDCOE to strengthen national digital security capacity to create a more transparent, responsive, and sustainable public accountability system.